HUBUNGAN POLA ASUH DEMOKRATIS ORANG TUA DAN PENDIDIKAN DEMOMRASI DI SEKOLAH DENGAN KEMANDIRIAN SISIWA/I KELAS VII SMP N 47 MUARO JAMBI - Ronika, Friska; Irzal Anderson; Dona Sariani (Civic Education Perspective Journal, 2022)
Based on the results of initial observations made by researchers at SMP N 47 Muaro Jambi, it showed problems related to the independence of students. The problem referred to in this research is the problem of independence that comes from the factors of parenting applied by parents and also the learning of democratic education that is received in the school environment. The purposes of this study was to determine the relationship of democratic parenting of parents and democratic education in schools to student independence. The data collection quantitative method used in this study is a quantitative method using a questionnaire. The analytical technique used is the analysis prerequisite test technique, namely normality and reability along with statistical hypothesis testing, namely statistical t test and F statistic test. The results of the research in this study are that individually both parenting democratic parents and democratic education in schools have a positive and significant relationship with the independence of students garde VII SMP N 47 Muaro Jambi. Then, together democratic education in schoos has a positive and significant relationship with student independence with a significance value of 0,0620 or in the strong category.Â  Â  Â